The overexpression, purification and complete amino acid sequence of chorismate synthase from Escherichia coli K12 and its comparison with the enzyme from Neurospora crassa. - White, P J (1988)
The enzyme chorismate synthase was purified in milligram quantities from an overproducing strain of Escherichia coli. The amino acid sequence was deduced from the nucleotide sequence of the aroC gene and confirmed by determining the N-terminal amino acid sequence of the purified enzyme. The complete polypeptide chain consists of 357 amino acid residues and has a calculated subunit Mr of 38,183. Cross-linking and gel-filtration experiments show that the enzyme is tetrameric. An improved purification of chorismate synthase from Neurospora crassa is also described. Cross-linking and gel-filtration experiments on the N. crassa enzyme show that it is also tetrameric with a subunit Mr of 50,000. It is proposed that the subunits of the N. crassa enzyme are larger because they contain a diaphorase domain that is absent from the E. coli enzyme.